ANALISIS FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA TENAGA KERJA PERUSAHAAN - Dwi Wahyuni, Maria Magdalena; Sahalessy, Yona; Blongkod, Fitriani Rahmatismi; Claartje, Masrikat Maya D.; Zil Fauzi, Ahmad (Ensiklopedia of Journal, 2024)
Hypertension is a disease defined as a persistent increase in blood pressure. Employees who work in large companies such as PT Hutama Karya Infrastructure undergo work, namely moving, pushing, lifting, and other activities that can increase blood pressure. Based on the absence of medical assessment of 147 workers, there are 10 workers (6.8%) experiencing hypertension. The purpose of the study was to determine the factors associated with the occurrence of hypertension in workers at PT Hutama Karya Insfrastruktur. The sample amounted to 137 people. Data collection tools using a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between work duration (p value 0.000), sleep patterns (p value 0.000), and diet (p value 0.000) to the incidence of hypertension. It is recommended that the company cooperate with the health team to be able to conduct regular health checks on all workers at PT. Hutama Karya Infrastruktur, make SOPs in accordance with the provisions, especially regarding work shifts and implement them.Keywords: Work Duration, Hypertension, Workers.